The heroic age of American invention - De Camp, L. Sprague (Doubleday, 1961)
Before the current era of great scientific research laboratories, the great inventors, working for the most part as individuals in their own small laboratories, accomplished the great feats which have revolutionized our civilization. Here are the stories of those feats and the dramatic personal lives of the men.